2019
DOI: 10.7150/ijms.29930
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29a is a key regulon that regulates BRD4 and mitigates liver fibrosis in mice by inhibiting hepatic stellate cell activation

Abstract: MicroRNA-29a is a key regulon that regulates hepatic stellate cells (HSCs) and mitigates liver fibrosis. However, the mechanism by which it does so remains largely undefined. The inhibition of bromodomain-4 protein (BRD4) represents a novel therapeutic target in hepatic fibrosis. Therefore, the purpose of this study is to investigate the miR-29a regulation of BRD4 signaling in a bile duct-ligation (BDL) animal model with regard to developing cholestatic liver fibrosis. Hepatic tissue in miR-29a transgenic mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…Overexpression of miR-29a can alleviate steatosis, NASH, and NASF in methionine-choline-deficient diet-fed mice [37]. Another of our studies also showed that overexpression of miR-29a counteracts fibrosis in murine liver by reducing DNMT1 and DNMT3b [39], as well as the down-regulation of methyl CpG binding protein 2 (MeCP2) [38].…”
Section: Mir-29a Functions As An Epigenetic Modifier To Mitigate Livesupporting
confidence: 57%
See 1 more Smart Citation
“…Overexpression of miR-29a can alleviate steatosis, NASH, and NASF in methionine-choline-deficient diet-fed mice [37]. Another of our studies also showed that overexpression of miR-29a counteracts fibrosis in murine liver by reducing DNMT1 and DNMT3b [39], as well as the down-regulation of methyl CpG binding protein 2 (MeCP2) [38].…”
Section: Mir-29a Functions As An Epigenetic Modifier To Mitigate Livesupporting
confidence: 57%
“…In NASH mouse model, we demonstrated that miR-29aTg provides protective effect through suppressing TGF-β and SMAD3 [37], two critical positive regulator of HSC activation [156]. Furthermore, we recently uncovered that anti-fibrotic effect of miR-29a is associated with inhibition of bromodomain-containing protein 4 (BRD4) in HSC [38], which represents a novel therapeutic target of liver fibrosis [157]. In view of using miR-29a as an interventional approach, Matsumoto et al have demonstrated that administration of miR-29a can reverse liver fibrosis in CCl 4 − and thioacetamide-treated mice.…”
Section: The Role Of Mir-29a In Fibrogenesismentioning
confidence: 99%
“…In addition, enhanced miR-29a expression has been shown to significantly decrease the free cholesterol accumulation in a hepatic steatosis cell model [23]. Our previous studies have demonstrated that miR-29a overexpression in cholestatic mice can significantly inhibit hepatocellular damage and liver fibrosis [24][25][26][27][28]. We further demonstrated that overexpression of miR-29a attenuates fatty acid uptake into the liver and the perturbation of hepatic mitochondrial biogenesis, leading to the prevention of hepatic steatosis, inflammation and fibrosis in the context of obesity-induced NAFLD [29].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, additional miRNAs seem to be involved in the fibrogenic activation of HSCs including miR-181 [ 36 , 37 ], miR-125b [ 38 ], and miR-214 [ 39 ] among others (see Review [ 34 ]). Interestingly, other miRNAs exert an inhibitory function towards liver fibrosis, such as miR-455-3p [ 40 ] and miR-29 [ 33 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%